The Role of the Principle of Balance in Agreements: Contract Validity and Annulment Under Indonesian Civil Law - Santoso, Santie Marlina; Listiana, Siti Parwitri; Lorendra, Chrispian; Adhinugroho, Yohanes Winarto; Prasetyo, Yosephine Sri Lestari; Azami, Takwim (LifeSciFi, 2025)
The principle of balance in agreements is essential to ensuring fairness in the formation and enforcement of contracts under Indonesian Civil Law. This principle dictates that the rights and obligations of both parties must be proportional, preventing any party from dominating the other. Although not explicitly mentioned in Article 1320 of the Indonesian Civil Code, the principle of balance is crucial for ensuring contracts reflect the genuine interests of both parties and avoid unfair advantages. It also intersects with the concepts of consensualism and freedom of contract, which allow parties to negotiate terms within legal and moral boundaries. However, abuses such as